A Semantic-Based Software Architecture for Processing Context Information in Ubiquitous Medicine - Rodrigues, Sérgio; Dilli, Renato; Costa, Cristiano; Barbosa, Jorge; Venecian, Luthiano; Yamin, Adenauer; Lopes, João; Souza, Rodrigo; Geyer, Cláudio (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2011: Anais do XII Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2011.17267, 2011)
Ubiquitous medicine aims to provide healthcare services at any time, without restriction of location, enhancing the mobility of health professionals. Considering this premise, in this paper we propose a software architecture model that integrates sensors and computing devices (mobile or fixed) in a ubiquitous environment, providing context-awareness service. This model, called uMED, uses semantic processing technologies in the contextual information acquisition and processing. To evaluate the uMED, we present a case study related to clinical monitoring of patients.